Short-circuit current analysis of DC distribution system in a ship with non-electric propulsion - Kurniawan, Adi; Gumilang, Ahlur Roi Novanto; Sarwito, Sardono; Budianto, Firman; Kurniawan, Akhmad Reinaldy (Institute of Advanced Engineering and Science, 2024)
Converting conventional AC radial shipboard distribution system to DC system has been recognized as a potential high impact solution to reduce ship’s fuel consumption. As big ships in Indonesia commonly use low voltage AC (LVAC) distribution system an effort to apply low voltage direct current (LVDC) distribution system without replace the propulsion system is a plausible choice. However, technical and economical investigations are required before recommendation to convert the shipboard distribution system to LVDC is officially launched. In this study, technical aspect in the term of short-circuit current is discussed. The goal of this study is to analyze how much the impact on the short-circuit current when LVDC system replaces LVAC system. The impact may affect the feasibility of LVDC system as the short-circuit current in a system dictate the scheme and capacity of the protection devices. Numerical simulations on a sample vessel are performed to obtain the profile of maximum short-circuit currents on all panels. The results show that the utilization of LVDC system decreases the short-circuit current by 10 times. Further investigations on the economic aspect needs to be performed to give clearer view of the feasibility of the LVDC system.